PENERAPAN METODE GREEN SCOR DALAM MENINGKATKAN KINERJA GREEN SUPPLY CHAIN MANAGEMENT DI PERUSAHAAN FARMASI - Christopher, Alvin; Saryatmo, Mohammad Agung; Andres (Universitas Tarumanagara, 2025)
The pharmaceutical industry has a significant impact on the environment, including air, soil, and water pollution caused by production waste. In an effort to address this issue, the implementation of Green Supply Chain Management (GSCM) has become a strategic and effective approach to improve operational efficiency while minimizing environmental impact. This study aims to evaluate the performance of Green Supply Chain Management (GSCM) in a pharmaceutical company using the Green Supply Chain Operations Reference (Green SCOR) approach. The Green SCOR framework includes five main elements: Plan, Source, Make, Deliver, and Return. This research uses a descriptive quantitative approach with primary data obtained through interviews, discussions, and questionnaires with relevant managers, as well as secondary data from company documentation. The evaluation results show that out of 30 performance indicators measured, 11 did not meet company standards, including raw material planning accuracy, material efficiency, transportation emissions, and recycling rates of solid and liquid waste. Therefore, a comprehensive evaluation was conducted by categorizing the findings into four dimensions: planning, production, distribution, and waste management. This study recommends the implementation of integrated systems, advancement of production technology, optimization of logistics, and strengthening of waste management systems to sustainably improve the performance of Green Supply Chain Management (GSCM).